Archaeological theory and scientific practice - Jones, Andrew, 1967- (Topics in contemporary archaeology., 2002)
Contemporary archaeology is polarised between 'scientists' who analyse, classify and describe, and social theorists, influenced by sociologies of science and culture theory. By emphasising the process of interpretation, this book shows that there is no necessary conflict between the aims and procedures of the various factions.